PENGUATAN LITERASI FIKIH MUAMALAH MAHASISWA FAKULTAS AGAMA ISLAM UNIZAR DALAM MENILAI HUKUM BUNGA BANK KONVENSIONAL DAN PRAKTIK PINJAMAN ONLINE MENGGUNAKAN PENDEKATAN BERPIKIR KRITIS - Herzi Fawaz (Nusantara Hasana Journal, 2026)
Muamalah fiqh literacy constitutes an essential competency for students of the Faculty of Islamic Studies in responding to the dynamics of contemporary financial transactions. The proliferation of conventional bank interest practices and online lending platforms requires students to possess the ability to understand and critically assess the relevance of such practices in light of Sharia principles through sound argumentation and critical reasoning. This study aims to analyze the enhancement of muamalah fiqh literacy among students of the Faculty of Islamic Studies at Unizar in evaluating the legal status of conventional bank interest and online lending practices through a critical thinking approach. The research employs a qualitative method with a case study design. Data were collected through in-depth interviews, group discussions, classroom observations, and document analysis in the form of student assignments. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the critical thinking approach effectively strengthens students’ muamalah fiqh literacy, as evidenced by their improved ability to identify elements of riba, analyze divergent scholarly opinions, and construct systematic legal arguments regarding conventional bank interest and online lending practices. Nevertheless, the study also reveals limitations in students’ initial conceptual understanding of contractual frameworks (ʿaqd) and the mechanisms of modern financial transactions. This research recommends the integration of case-based and critical thinking-oriented muamalah fiqh instruction as a strategic approach to strengthening Islamic legal literacy in higher education institutions.